The utilization and desaturation of oleate and linoleate during glycerolipid biosynthesis in olive (Olea europaea L.) callus cultures - Hernández, M Luisa (Journal of experimental botany, 2008)
Callus cultures from olive (Olea europaea L.) were used to study characteristics of desaturation in this oil-rich tissue. The incorporation of [1-(14)C]oleate and [1-(14)C]linoleate into complex lipids and their further desaturation was followed in incubations of up to 48 h. Both radiolabelled fatty acids were rapidly incorporated into lipids, especially phosphatidylcholine and triacylglycerol. Radiolabelling of these two lipids peaked after 1-4 h, after which it fell. In contrast, other phosphoglycerides and the galactosylglycerides were labelled in a more sustained manner. [1-(14)C]Linoleate was almost exclusively found in the galactolipids. With [1-(14)C]linoleate as a precursor, the only significant desaturation to linolenate was in the galactolipids. Monogalactosyldiacylglycerol was the first lipid in which [1-(14)C]linoleate and [1-(14)C]linolenate appeared after incubation of the calli with [1-(14)C]oleate and [1-(14)C]linoleate, respectively. The presence of radioactivity in the plastidial lipids shows that both [1-(14)C]oleate and [1-(14)C]linoleate can freely enter the chloroplast. Two important environmental effects were also examined. Raised incubation temperatures (30-35 degrees C) reduced oleate desaturation and this was also reflected in the endogenous fatty acid composition. Low light also caused less oleate desaturation. The data indicate that lysophosphatidylcholine acyltransferase is important for the entry of oleate and linoleate into olive callus lipid metabolism and phospholipid:diacylglycerol acyltransferase may be involved in triacylglycerol biosynthesis. In addition, it is shown that plastid desaturases are mainly responsible for the production of polyunsaturated fatty acids. Individual fatty acid desaturases were differently susceptible to environmental stresses with FAD2 being reduced by both high temperature and low light, whereas FAD7 was only affected by high temperature